Things we couldn't say - Coles, Jay (Scholastic Press, 2021)
"There's always been a hole in Gio's life. Not because he's into both guys and girls. Not because his father has some drinking issues. Not because his friends are always bringing him their drama. No, the hole in Gio's life takes the shape of his birth mom, who left Gio, his brother, and his father when Gio was nine years old. For eight years, he never heard a word from her . . . and now, just as he's started to get his life together, she's back" -- Jacket flap.